Performance analysis of ship mounting PV panels deployed in Sungsang Estuary and Bangka Strait, Indonesia - Afiz Zullah; Tresna Dewi; Rusdianasari Rusdianasari (SINERGI, 2024)
In an archipelago country like Indonesia, maritime transportation is essential. However, the ships, like other modes of transportation, burn fuel, contributing to CO2 emissions and negatively impacting marine life. Alternative renewable energy can help solve this problem while being environmentally friendly and cost-effective. As a result, this research describes installing PV systems to power electronic loads on a pilot ship. The supply-demand scenario was simulated using the System Advisory Model. The experiment lasted 176 days, 32 of which were still hybrid with a diesel generator, and for 144 days, electronics loads were entirely powered by PV systems. The experimental results show that the generated power consistently exceeds what is necessary. MPPT may also control the battery charging to avoid overcharging by ensuring the voltage input is always consistent. The maximum generated power is 2356 W with a peak load of 1669 W, and the average generated power is 1645 W with a load of 720.6 W. According to SIMAPRO's life cycle study results, the most significant environmental impact comes during installation due to using diesel fuel trucks and when the PV system is no longer operational since it will become a landfill, harming the ecosystem. PV systems, on the other hand, have no environmental impact during installation. Economic estimates show significant savings and, of course, profits.